Microscopy and phylogeny of Pyramimonas tatianae sp. nov. (Pyramimonadales, Chlorophyta), a scaly quadriflagellate from Golden Horn Bay (eastern Russia) and formal description of Pyramimonadophyceae classis nova. Issue 1 (2nd January 2020) - Daugbjerg, Niels; Fassel, Nicolai M.D.; Moestrup, Øjvind
ABSTRACT: Nearly two decades ago a scaly quadriflagellate culture was established from a sample collected in Golden Horn Bay, eastern Russia. Here we present a comparative analysis of pheno- and genotypic characters and show that the isolate did not match any existing species of Pyramimonas and is therefore described as P. tatianae sp. nov. The species was probably identified as P . aff. cordata in previous studies on material from the same area. Based on an ultrastructural account of the cell and its external body scales it was found to belong to the subgenus Vestigifera . This was supported by a phylogenetic analysis using the chloroplast-encoded rbc L gene. The cell dimensions of P. tatianae were 6–7 µm long and 5–6 µm wide and it thus represented one of the smaller species of the genus. The cup-shaped chloroplast was divided into four lobes reaching from the middle to the anterior part of the cell. A single posterior eyespot was observed adjacent to an excentric pyrenoid. The ultrastructure of the body and flagellar scales were illustrated from material prepared for whole mounts and thin sections. The new species was compared with P. cordata and P. mitra, two other vestigiferans with which it shares some morphological features. The sequence divergence between P. tatianae and the most closely related species, P. mitra, was 2.5%. The phylogeny of Vestigifera revealed two lineages, one comprising cold-water species and the cosmopolitan P. orientalis, and the other species from temperate-subtropical waters. The tree topology suggested a southbound dispersal route. This was further supported by all antarctic Pyramimonas species having encystment stages as part of their life cycle. It was therefore probable that their ancestors also were capable of producing cysts allowing transportation over great distances. A formal description of the class Pyramimonadophyceae comprising both extant and extinct species was also provided.